Association Between Maternal Lifestyle and Risk of Metabolic Syndrome in Offspring—A Cross-Sectional Study From China - Li, Yanhui (Front Endocrinol (Lausanne), 2020)
BACKGROUND: The prevalence of MS among children and adolescents continues to rise, which has become an escalating serious health issue worldwide. It had been reported that maternal current lifestyle had a strong independent correlation with offspring health. However, it is not clear whether comprehensive lifestyle of mother has an impact on the MS risk in offspring and the role of offspring’s lifestyle in it. METHODS AND RESULTS: We included 4,837 mother-child pairs from a multi-centered cross-sectional study conducted in China. The information of maternal lifestyle was obtained by self-reported questionnaire, and metabolic syndrome (MS) in offspring was determined by anthropometric measurements and blood tests. Logistic regression models were employed to evaluate the association between maternal lifestyle and risk of MS in offspring. We found maternal healthy lifestyle was independently associated with lower risk of offspring MS, and the risk of MS in offspring decreased with the increased number of maternal ideal lifestyle factors. Although adolescents’ lifestyle did not fully explain the relationship between maternal lifestyle and risk of offspring MS, compared with those had less ideal lifestyle factors in both mothers and offspring, the risk of offspring MS was lower in those had more ideal lifestyle factors in both mothers and adolescents. CONCLUSIONS: Healthy lifestyle in mothers was associated with a lower risk of MS in offspring, which was independent of offspring’s lifestyle. These findings support mother-based lifestyle intervention could be an effective strategy to reduce the MS risk in adolescents.